(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The central feature of liberal democratic government is representation between men and women in political activity. Both men and women must have an equal opportunity to engage equally in all respects and in all stages of democratic systems in accordance with international norms. While in many countries women have taken great strides in securing a vote and the right to be elected to political positions, they make up less than 11. While different legislative enactments and commissions for supporting gender equality have been created, gender differences continue to occur, particularly in the political arena. Encouraging women in politics is one of female empowerment’s key fields. The participation of women at the policy level not only improves their social, political and economic status, but also reinforces public structures by enhancing their inclusiveness and purpose. While women have made greater progress, because of political, socioeconomic, ideological and psychological factors they still cannot engage in politics. Women’s fair representation in this framework must also be analyzed in the proper way in order to provide good democratic governance. There will be no true democracy if we neglect or put aside the voices and problems of women that make up half of the country’s population. This paper analyses women’s difficulties, voting behavior and problems in national and local government.